Targeted proteomics identifies circulating biomarkers associated with active COVID-19 and post-COVID-19 - Zoodsma, Martijn; de Nooijer, Aline H.; Grondman, Inge; Gupta, Manoj Kumar; Bonifacius, Agnes; Koeken, Valerie A. C. M.; Kooistra, Emma; Kilic, Gizem; Bulut, Ozlem; Gödecke, Nina; Janssen, Nico; Kox, Matthijs; et al. (Frontiers in Immunology, 2022)
The ongoing coronavirus Coronavirus disease Disease 2019 (COVID-19) pandemic is caused by the highly infectious severe Severe acute Acute respiratory Respiratory syndrome Syndrome coronavirusCoronavirus-2 (SARS-CoV-2). There is an urgent need to identifyfor biomarkers that will help in better stratification of patients and contribute to personalized treatments. We performed targeted proteomics using the Olink platform and systematically investigated protein concentrations in 350 hospitalized COVID-19 patients, 186 post-COVID-19 individuals, and 61 healthy individuals from 3 independent cohorts. Results revealed a an acute SARS-CoV-2 infection signature of acute SARS-CoV-2 infection, which is represented by inflammatory biomarkers, chemokines and complement-related factors. Furthermore, the post-COVID-19 proteomic dynamics showed that the circulating proteome is still significantly affected in post-COVID-19 samples by the disease several weeks after the infection phase. Post-COVID-19 individuals are characterized by upregulation of mediators of the tumor necrosis (TNF)-α signaling pathways and proteins related to transforming growth factor (TGF)-ß. TheIn addition, Tthe circulating proteome is able to differentiate between patients with previous different COVID-19 disease severities, and is associated to with the time after infection. These results provide important insights into changes induced by SARS-CoV-2 infection at the proteomic level by integrating several cohorts to obtain a large disease spectrum, including variation in disease severity and time after infection. These findings could guide the development of host-directed therapy in COVID-19.